2007
DOI: 10.1088/0953-8984/19/26/266203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co doping on the structural, optical and magnetic properties of ZnO nanoparticles

Abstract: We report the results of a detailed investigation of sol-gel-synthesized nanoscale Zn(1-x)Co(x)O powders processed at 350 °C with 0≤x≤0.12 to understand how the structural, morphological, optical and magnetic properties of ZnO are modified by Co doping, in addition to searching for the theoretically predicted ferromagnetism. With x increasing to 0.03, both lattice parameters a and c of the hexagonal ZnO decreased, suggesting substitutional doping of Co at the tetrahedral Zn(2+) sites. For x>0.03, these trends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 81 publications
5
66
0
Order By: Relevance
“…Considering next the visible spectral range, we note that while it has been reported that PL decreases with increasing Co doping [37] significant PL persists in Co-doped ZnO samples of various types [14,23,29,38]. Starting at the short-wavelength end of the visible, a violet band, centered at 2.96 eV, due to zinc interstitials (Zn i ) appears in the case of the ZnO film.…”
Section: Photoluminescencementioning
confidence: 81%
See 1 more Smart Citation
“…Considering next the visible spectral range, we note that while it has been reported that PL decreases with increasing Co doping [37] significant PL persists in Co-doped ZnO samples of various types [14,23,29,38]. Starting at the short-wavelength end of the visible, a violet band, centered at 2.96 eV, due to zinc interstitials (Zn i ) appears in the case of the ZnO film.…”
Section: Photoluminescencementioning
confidence: 81%
“…Hays et al [37] observed a progressive attenuation of the E 2 mode with increasing Co concentration in ZnO which they attributed to increased strain induced by an increase in the density of Co occupying interstitial sites. Here, however, with the less heavily doped samples (ZC1 and ZC2) displaying attenuation of the 439 cm -1 peak, we suggest that in these cases the origin of the strain…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Doping induces drastic changes in its optical, electrical and magnetic properties by modifying its electronic structure. [11][12][13] Different methods have been used for the synthesis of doped ZnO such as laser ablation, 14 magneton sputtering, 15 high temperature calcinations, 16 sol-gel, 17 hydrothermal 18 and sonochemical methods 19 . Among these techniques, sonochemical method has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
“…The peak at 490 cm −1 is assigned to the most probable impurity phase, Co 3 O 4 [22]. This impurity phase wasn't observed in XRD measurements, possibly due to its relatively low concentration, which makes it difficult to detect.…”
Section: Resultsmentioning
confidence: 99%
“…Co 2+ exchange pairs were observed by EPR in singlecrystalline Zn 1−x Co x O thin films in the very low doping regime, x = 0 03 [33]. If Co pairs could be formed at higher doping concentrations, those Co ions would not be expected to contribute to the EPR spectrum representing the isolated impurities [34]. A careful analysis of our EPR spectra does not show any signature corresponding to Co pairs and therefore, we did not include in Eq.…”
Section: Resultsmentioning
confidence: 99%